Critical Thinking in Multimodal ELT Materials: A Discourse Analysis of Tasks and Visuals in Bahasa Inggris Tingkat Lanjut (Grade XI) - Dea Ayu Lestari (Utan Kayu Publishing, 2025)
Critical thinking is a very important skill in English Language Teaching (ELT), especially in learning contexts that still rely heavily on textbooks as the main source. This study aims to examine how critical thinking skills are represented in multimodal ELT learning resources. The analysis focuses on the relationship between learning activities and visual elements in Advanced English textbooks for grade 11, to determine the extent to which these two aspects support each other in fostering students' critical thinking skills. The research is based on the premise that the development of critical thinking is influenced not only by verbal instructions but also by the purposeful integration of visual modes. Adopting a qualitative research approach, the study applied multimodal discourse analysis to selected information-dense tasks that incorporate both textual directives and visual components. The analysis examined task categories, cognitive demands according to Bloom’s revised taxonomy, visual functions, and markers of critical thinking. The results of the study indicate that critical thinking skills can be developed through pedagogical alignment between learning tasks and visual elements. The results of the study indicate that narrative images can develop analytical and evaluative skills, ideologically charged visuals support critical assessment and argument development, while conceptual visuals help students organize analysis and interpret ideas creatively. These findings confirm that visual elements only play an effective role in improving higher-order thinking skills when consciously designed and combined with tasks that require complex cognitive processes, thus emphasizing the importance of planned multimodal design in ELT teaching materials.